Contribution of transcript stability to a conserved procyanidin-induced cytokine response in γδT cells - Daughenbaugh, Katie F. (2011)
γδ T cells function in innate and adaptive immunity and are primed for secondary responses by procyanidin components of unripe apple peel (APP). Here we investigate the effects of APP and purified procyanidins on γ δ T cell gene expression. A microarray analysis was performed on bovine γ δ T cells treated with APP; increases in transcripts encoding GM-CSF, IL-8, and IL-17, but not markers of TCR stimulation such as IFNγ , were observed. Key responses were confirmed in human, mouse, and bovine cells by RT-PCR and/or ELISA, indicating a conserved response to procyanidins. In vivo relevance of the cytokine response was shown in mice following intraperitoneal injection of APP, which induced production of CXCL1/KC and resulted in neutrophil influx to the blood and peritoneum. In the human γ δ T cell-line, MOLT-14, GM-CSF and IL-8 transcripts were increased and stabilized in cells treated with crude APP or purified procyanidins. The ERK1/2 MAPK pathway was activated in APP-treated cells, and necessary for transcript stabilization. Our data describe a unique γ δ T cell inflammatory response during procyanidin treatment and suggest that transcript stability mechanisms could account, at least in part, for the priming phenotype.